Autophagy-deficient Kupffer cells promote tumorigenesis by enhancing mtROS-NF-κB-IL1α/β-dependent inflammation and fibrosis during the preneoplastic stage of hepatocarcinogenesis. (1st March 2017) - Sun, Kai; Xu, Lingyun; Jing, Yingying; Han, Zhipeng; Chen, Xiaojing; Cai, Chenlei; Zhao, Peipei; Zhao, Xue; Yang, Liqun; Wei, Lixin
Abstract: As a cellular degradation mechanism, autophagy exerts crucial and complicated effects on HCC development. Liver non-parenchymal cells, including hepatic resident macrophage Kupffer cells, also play important roles in this process. However, most associated studies have focused on the influence of the autophagy level in hepatic cells and HCC cells, but not liver non-parenchymal cells. Based on our previous study, we confirmed that Atg5 silence in the liver during the preneoplastic stage facilitated liver fibrosis, inflammation and, ultimately, tumorigenesis. We further found that autophagy deficiency promotes the production of inflammatory and fibrogenic factors in macrophages. Moreover, Kupffer cell depletion rescued the tumor-promoting effect of autophagy deficiency during the preneoplastic stage. In autophagy-deficient macrophages, mitochondrial ROS mediated inflammation- and fibrosis-promoting effects by increasing IL1α/β production via enhancing NF-κB-associated pathways. Both blocking of mitochondrial ROS and blocking the IL1 receptor stopped the promotion of fibrosis, inflammation and tumorigenesis resulting from Atg5 knockdown during the preneoplastic stage. In conclusion, autophagy-deficient Kupffer cells promote liver fibrosis, inflammation and, finally, hepatocarcinogenesis during the preneoplastic stage by enhancing mitochondrial ROS- NF-κB-IL1α/β pathways. Highlights: Atg5 defect at preneoplastic stage reduces inflammation, fibrosis and tumorigenesis. Autophagy defect in KCs assist in the tumor-promoting effects of autophagy deficiency. Autophagy-deficient KCs facilitate inflammation and fibrosis by increasing IL1α/β. IL1α/β secretion relies on mtROS and NF-κB in autophagy-deficient macrophages. Both anakinra and mito-Q reverse the tumor-promoting effects of Atg5 inhibition.